2019
DOI: 10.1055/s-0039-1693737
|View full text |Cite|
|
Sign up to set email alerts
|

All-Trans Retinoic Acid Impairs Platelet Function and Thrombus Formation and Inhibits Protein Kinase CßI/δ Phosphorylation

Abstract: All-trans retinoic acid (ATRA) is widely used for induction of complete remission in patients with acute promyelocytic leukemia (APL). ATRA also regulates protein kinase C (PKC) activity. Therapeutic use of ATRA reportedly interferes with hemostatic function in APL patients, including effects on coagulation or other vascular cells, although effects of ATRA on platelets remain unclear. This study aims to investigate the effect of therapeutic-relevant doses of ATRA on platelet function. Human platelets were prei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…RA reduced platelet activation in dietinduced atherosclerosis in rabbits, 44 and inhibited platelet aggregation, spreading, dense-granule secretion, and clot retraction in vitro. 45 While we cannot exclude a contribution of the increased number of thrombocytes, possible direct effects of RA include thrombocyte responses to injury, or even an increased production of other key coagulation factors through the same mechanism as behind increased fibrinogen production (mediated by RA and the retinoid X nuclear receptors 36 ), our data showed a trend toward increased thrombocyte binding after RA treatment that correlated with increased fibrinogen.…”
Section: Thrombosis and Haemostasismentioning
confidence: 56%
“…RA reduced platelet activation in dietinduced atherosclerosis in rabbits, 44 and inhibited platelet aggregation, spreading, dense-granule secretion, and clot retraction in vitro. 45 While we cannot exclude a contribution of the increased number of thrombocytes, possible direct effects of RA include thrombocyte responses to injury, or even an increased production of other key coagulation factors through the same mechanism as behind increased fibrinogen production (mediated by RA and the retinoid X nuclear receptors 36 ), our data showed a trend toward increased thrombocyte binding after RA treatment that correlated with increased fibrinogen.…”
Section: Thrombosis and Haemostasismentioning
confidence: 56%
“…Interestingly, flocoumafen has been found to actively accumulate in the liver (Huckle et al 1988), where this pesticide is frequently found in wildlife (Alabau et al 2020). The extensive relationship among retinoic acid homeostasis, obesity, insulin resistance, and coagulation (Mody 2017; Luo et al 2019) clearly gives flocoumafen an important role as an environmental pollutant involved in metabolic syndrome—a systems biology finding that deserves special attention.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet aggregation was conducted in the presence of fibrinogen (0.5 mg/ml) as described previously (Luo et al, 2019;Wei G. et al, 2020). After matrine treatment, platelet aggregation induced by CRP (0.1 μg/ml) or thrombin (0.04 U/ml) was analyzed in a Lumi-Aggregometer Model 700 (Chrono-log Corporation, Havertown, PA, United States) at 37°C with stirring (1,000 rpm).…”
Section: Platelet Aggregation and Atp Releasementioning
confidence: 99%
“…Platelet α-granule secretion was assessed via measuring P-selectin expression and integrin αIIbβ3 activation was evaluated via detecting the activation-dependent binding of PAC-1 to platelet αIIbβ3 by flow cytometry as described previously (Luo et al, 2019;Wei G. et al, 2020). Briefly, after matrine treatment, platelets were stimulated with CRP (0.1 or 2 μg/ml) or thrombin (0.04 or 0.5 U/ml) in the presence of PE-conjugated anti-P-selectin antibody or FITC-conjugated PAC-1 antibody followed by measuring P-selectin expression or PAC-1 binding by flow cytometry using FITC-conjugated mouse anti-human CD41a to set the platelet gate in the Forward Scatter and Side Scatter.…”
Section: Platelet α-Granule Secretion and αIibβ3 Activationmentioning
confidence: 99%
See 1 more Smart Citation